2016
DOI: 10.1017/s1751731115002372
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between rabbit semen characteristics and fertilising ability after insemination

Abstract: This study aimed to analyse the relationship between rabbit semen characteristics and semen fertilising ability after insemination, which is generally found to be weak. Our hypothesis was that using high semen dilutions (1 : 19), non-oestrus-stimulated does, and homospermic inseminations would make it easier to predict semen fertilising ability. Semen characteristics were evaluated on 275 ejaculates of 128 INRA1001 bucks, distributed into five successive batches. A total of 1970 inseminations were performed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
(28 reference statements)
1
6
0
Order By: Relevance
“…This conclusion was actually based on the analytical findings of the seminal samples collected once a week from rabbit bucks fed on ration treated with soybean and sunflower oils. According to Castellini and Lattaioli (1999), estimating semen quality is important in determining the reproductive efficiency in rabbit bucks, where it has been documented to be correlated with sperm fertilizing ability (Castellini et al, 2000;Brun et al, 2002;Hagen et al, 2002;Castellini, 2007;Piles et al, 2013;Theau-Clément et al, 2016). The present data indicated that semen collected from rabbit bucks supplemented with vegetable oils had higher sperm concentration, total sperm output, percentage of motile sperms, as well as lower percentages of dead and altered acrosomal sperms than the control bucks.…”
Section: Discussionsupporting
confidence: 51%
“…This conclusion was actually based on the analytical findings of the seminal samples collected once a week from rabbit bucks fed on ration treated with soybean and sunflower oils. According to Castellini and Lattaioli (1999), estimating semen quality is important in determining the reproductive efficiency in rabbit bucks, where it has been documented to be correlated with sperm fertilizing ability (Castellini et al, 2000;Brun et al, 2002;Hagen et al, 2002;Castellini, 2007;Piles et al, 2013;Theau-Clément et al, 2016). The present data indicated that semen collected from rabbit bucks supplemented with vegetable oils had higher sperm concentration, total sperm output, percentage of motile sperms, as well as lower percentages of dead and altered acrosomal sperms than the control bucks.…”
Section: Discussionsupporting
confidence: 51%
“…According to Araujo et al (2013), using suitable insemination dose and dilution rate are very important because very small volumes may result in less effective mechanical drainage, while highly concentrate semen may be more irritating because of more contacts between spermatozoa and endometrium, resulting in an intense inflammatory response. Theau-Clément et al (2016) showed that the presence or absence of gel, volume, percentage of progressive sperms, curvilinear velocity and beat frequency of the flagellum, did not affect fertility or productivity of inseminated INRA1001 rabbit doe. However, mass motility and the percentage of motile cells (>84%) significantly influenced rabbit doe productivity, but there was a non-linear relationship.…”
Section: Semen Quality and Site Of Inseminationmentioning
confidence: 94%
“…The main factors related to the quality of the semen are fertility in females (proportion of pregnant females after AI), and prolificacy (number of offspring per litter), as pointed out by IRRG (2005). Indeed, a correlation between sperm motility, concentration and female reproductive performance has been demonstrated in several studies (Brun et al, 2002;Theau-Clément et al, 2016).…”
Section: Introductionmentioning
confidence: 91%
“…The other 8.5 mL of the semen pools were used to carry out the insemination doses in 0.5 mL straws (IMV Technologies, L'Aigle, France) with a total of around 24 million sperm cells per dose (484.5±122.2 million spermatozoa/mL in raw ejaculates) (Theau-Clément et al, 2016). Doses were prepared only from semen pools with a total motility above 70% (Daniel and Renard, 2010) and diluted in the medium with the original antibiotic composition (original) or new antibiotic composition (gentamicin 0.3 g/L; New).…”
Section: Semen Collection For Motility Analysis and Dose Packagingmentioning
confidence: 99%